Learning Assistance using Image Media in Increasing Reading Interest of Students of Grade 1 Madrasah Ibtidaiyah Darul ' Ula Tarokan Lor Village - Uswatun Hasanah; Ribut Prastiwi Sriwijayanti; Maulidza Wijayanti; Windi Soleha; Zulkha Suharwati (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity was motivated by the use of image media in increasing students' reading interest. learning that is used by someone by using a tool made to facilitate the delivery of material when teaching at school. There are still many schools that are only concerned with cognitive aspects without looking at student learning problems, thus making students bored and lazy to study. The importance of using picture media is that teaching attracts students' attention and teaching materials will be more clearly understood by students. The implementation method in this service is the preparation, implementation, and unstructured interviews. The results of learning assistance using image media have a positive impact on both students and teachers, this can be seen from the results of interviews revealed by the homeroom teacher of class 1 MI and the responses of students and teachers who feel helped by the existence of learning mentoring activities because this activity makes students become better to understand the material being taught.